Confesión, culpa y penitencia: construcciones de la alteridad. Una lectura a “La tercera orilla del río” ((Dossier Seis miradas al cuerpo y al deseo de una poética latinoamericana desde hace cinco siglos) - Correa, Mariagusta (2017)
The article analyzes these three motives: confession, guilt and penance, in the story “La tercera orilla del río” of the book Primeras historias (1962), by João Guimarães Rosa (1908- 1967), to raise the issue of construction of an alterity only possible after the sacrificial act and within an economy of penance, which requires a rupture with its previous form of life, in order to reaffirm the transcendence associated with the idea of mortification, and symbolized in the perpetuity of the river in which the father sails and in which the son also wishes to sail. The identification of guilt through confession, and penance and its severity make evident the transformation of one of the characters, and drive the dynamic confession/penance that father and son need to re-signify their condition as human beings, precisely, from, on the one hand, the recognition of their faults, as a condition for the own expiation, and, on the other, through the production of a plot in which the symbols of Judeo-Christian tradition are interwoven, the exercise of memory and the reconstruction of the facts.